Assessment of remotely-sensed sea-surface temperature and chlorophyll-a concentration in San Matías Gulf (Patagonia, Argentina) - Williams, Gabriela Noemí (2013)
Field measurements of surface temperature and chlorophyll-a concentration were used to evaluate for the first time the performance of the standard sea surface temperature and chlorophyll-a algorithms of the Moderate Resolution Imaging Spectroradiometer (MODIS) in San Matías Gulf, northern of the Argentine Patagonian Continental Shelf (between 40°47'S and 42°13'S). The fit of the temperature data to a Standard Major Axis (SMA) type II regression model indicated that a high proportion of the total variance (r 2 ≥0.80) was explained by the model. For chlorophyll-a, the low correlation (r 2 =0.15) and high dispersion indicated a poor performance and a general overestimation of Chl-a by the OC3Mv5 algorithm as indicated by the Relative Percent Difference (RPD=113%). However, for stations located in the northern area of the gulf the result showed a higher correlation (r 2 =0.76) and less dispersion (RPD=31%). The feasible reasons and explanations for the performance of NLSST and OC3Mv5 algorithms are discussed. The results of the temporal variability analysis of SST and Chl-a in different areas of the gulf agreed with previous studies.